A Critical Inquiry Into the Field of Multinational Research on Women's Offending - Applin, Samantha (European journal on criminal policy and research, 2020)
This paper provides a comprehensive and critical look at the current state of multinational research on women's offending and scrutinizes how this knowledge has been derived. The importance of global research for theoretical advancement is discussed. Questions about the validity of official data estimates as proxies for women's offending in cross-national research focus on the extent to which research findings are reflecting behavioural differences among the populations being studied or other exogenous factors, such as policing, policy and data collection. This paper carries on a tradition of inquiry into the data by presenting visual heuristics to facilitate easy interpretation of definitional differences in specified crime types across time and between country and by determining societal factors that correlate with the "dark figure of crime" when contrasting arrests and reported victimization across nations. The findings suggest cautious optimism for proceeding with rigorously compiled multinational official data sources to advance this important field of work.